Model Pembelajaran Kooperatif Jigsaw terhadap Hasil Belajar Anatomi Fisiologi Perawatan Dasar - I Nyoman Ribek; I Gusti Ketut Ngurah (Jurnal Gema Keperawatan, 2016)
This Study was aimed at finding out the effect of cooperative learning model on the Basic Care for Physiological Anatomy learning achievement by controlling students’ prior knowledge. This study was a quasi-experimental research using the 2x2 factorial design involving 80 students of the Department of Health Care of Politeknik Kesehatan Denpasar as the sample. The data were analyzed using analysis of covariance. After controlling prior knowledge, the result showed that the Basic Care for Physiological Anatomy Learning achievement of the group of students who learned through the Jigsaw type Cooperative Learning model was higher than that of those who learned through the STAD type Cooperative Learning modell In the light of the findings it can be inferred that to obtain an optimum level in the learning achievement, beside selecting an appropriate learning model, the teacher should also use an appropriate technique of assessment.Budiawan dan Alit Arsani. “Pengaruh Model Pembelajaran Kooperatif Tipe Jigsaw terhadap Prestasi Belajar Ilmu Fisiologi Olahraga.“ Jurnal Pendidikan Indonesia, Vol. 2, No.1, 2013, hh. 135-140. DePorter, Bobbi. Quantum Teaching terjemahan Alwiyah Abddurrahman. Bandung: Kaifa, 2000. Djaali dan Puji Muljono. Pengukuran dalam Bidang Pendidikan. Jakarta: PPS UNJ, 2004. Jurusan Keperawatan Poltekes. Laporan Hasil Belajar Jurusan Keperawatan. Laporan Tahunan (Denpasar: Politeknik Kesehatan, 2009), hh. 8-12 Rika Aulia Syofyanti. ” Hubungan Pelayanan Keperawatan Gawat Darurat dengan Tingkat kepuasan Pasien.“ http:// contentJurnal-Richa pdf.pdf, 20014, hh. 3-13. Santrock, John W. Psikologi Pendidikan, terjemahan Tri Wibowo B.S. Jakarta: Kencana, 2008. Soeparman. Pedoman Penyusunan Kurikulum Pendidikan Tenaga Kesehatan. Jakarta: BPPSDM Kesehatan Press, 2009. Sugianto, Dian Armanto, dan Mara Bangun Harahap. “Perbedaan Pembelajaran Kooperatif Jigsaw dan Kooperatif STAD Ditinjau dari Kemampuan Penalaran dan Komunikasi Matematika SMA. Jurnal Didaktik Matematika, Volume 1 No.1, 2014, hh. 90- 98. Sunilawati, Ni Made Sunilawati, Nyoman Dantes, dan I Made Candiasa. “Pengaruh Model Pembelajaran Kooperatif STAD terhadap Prestasi Belajar Matematika Ditinjau dari Kemampuan Numeric